A set of manganese ion activated fluoride phosphors (A2BF6:Mn4+, A = K, Na, B = Si, Ge, Ti): synthesis below 0 °C and efficient room-temperature photoluminescence. Issue 40 (3rd October 2016) - Tang, Fei; Su, Zhicheng; Ye, Honggang; Wang, Mingzheng; Lan, Xin; Phillips, David Lee; Cao, Yongge; Xu, Shijie
Abstract : Transition-metal ion activated solid-state phosphors are of particular interest for the development of LED-based white light sources. Abstract : Transition-metal ion activated solid-state phosphors are of particular interest for the development of LED-based white light sources. In addition to their relatively low cost, these luminescent materials show exceptionally high luminescence efficiency, especially at room temperature and above, due to the involvement and promotion of thermal phonons. In this article, we present a comprehensive investigation into a set of manganese ion doped fluoride phosphors (A2 BF6 :Mn 4+, A = K, Na, B = Si, Ge, Ti), including the synthesis procedures and various characterization, with the emphasis on optical spectroscopic characterization. All of the phosphors synthesized at a temperature of −16 °C using a chemical co-precipitation method exhibit intense red color emission at room temperature under the excitation of light, with a wide range of wavelengths from 450 nm to 325 nm. In most of the phosphors, phonon-assisted luminescence dominates the spectra, which is evidenced using Raman scattering measurements. X-ray diffraction data from the samples reveal that K2 SiF6 :Mn 4+ crystallizes in a cubic phase, while the remaining crystals have hexagonal structures, but with different symmetries for K2 TiF6 :Mn 4+ and Na2 SiF6 :Mn 4+ . More interestingly, well-resolved spectral splitting was observed in the major phonon-assisted luminescence signatures of both the K2 SiF6 :Mn 4+ and K2 TiF6 :Mn 4+ samples, indicating the occurrence of complicated but fascinating phonon-assisted transition processes in the phosphors.